Chemical recycling of bioplastics: technical opportunities to preserve chemical functionality as path towards a circular economy. Issue 24 (22nd November 2022) - Merchan, Angel L.; Fischöder, Thomas; Hee, Johann; Lehnertz, Marcus S.; Osterthun, Ole; Pielsticker, Stefan; Schleier, Julia; Tiso, Till; Blank, Lars M.; Klankermayer, Jürgen; Kneer, Reinhold; Quicker, Peter; et al.
Abstract : We herein present a detailed overview of recycling techniques for common bioplastics including a detailed evaluation by life cycle assessment. Abstract : Plastics have become an integral part of many areas of life. Their high chemical resistance has opened a huge range of applications. At the same time, this creates major challenges for the environment, so those plastic residues can now be found even in the remotest corners of the earth. The goal of the circular economy is to address this challenge by utilizing residual and waste streams as valuable raw materials. With suitable recycling strategies into the original or even added-value applications, driving forces for properly closed carbon cycles become available. In recent years, bioplastics possess tremendous growth rates. Biomass-based, they theoretically enable closed carbon cycles as their carbon atoms are harvested from CO2 by photosynthesis. Despite this advantage, their increasing market penetration must be accompanied by appropriate recycling technologies enabling sustainable and economic utilization of the chemically synthesized building blocks. This minireview addresses current knowledge on the (bio)chemical and thermal recycling of chemically novel bioplastics, that is biomass-based plastics not resembling the chemical structure of well-established fossil-derived plastics; major emphasis is on maintaining chemical functionality of the bioplastic building blocks. Available methodologies for thermal (gasification, pyrolysis), chemo-catalytic (homogeneous and heterogeneous catalysis) and bio-catalytic (enzymatic and whole-cell catalysis) recycling are summarized together with the available insights of LCA studies on recycling strategies for chemically novel biomass-based plastics. The literature review shows that although mechanical recycling presents currently the most attractive technology, LCA studies emphasize the potentially lower environmental impact of chemical recycling compared with other End-of-Life (EoL) solutions. Therefore, early development of viable technologies for chemical recycling in the growing field of biomass-based plastics is of utmost importance.